2018
DOI: 10.22456/2316-2171.75904
|View full text |Cite
|
Sign up to set email alerts
|

Idosos E Inclusão Digital Com Tablet-Pc: Uma Revisão Sistemática Da Literatura

Abstract: Objetivo: Revisão sistemática de pesquisas de intervenção em idosos acerca do uso de tablet para identificar os ganhos e as dificuldades no uso e na adesão desse tipo de dispositivo móvel. Métodos: Levantamento de estudos publicados entre janeiro de 2010 até novembro de 2017 nas bases de dados Lilacs, AgeLine, PubMed, Web of Science, Periódicos CAPES utilizando os descritores: TIC e idosos, inclusão digital e idosos, aprendizado digital e idosos, dispositivos móveis e idosos, tablet e idosos, e os termos em in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…These findings corroborate a systematic review 2 on computerized cognitive training, which found a significant improvement in the cognitive and psychological characteristics of healthy older adults. Likewise, the study by Ordonez et al, 6 involving cognitive training with computer games in the elderly, also observed positive effects in the assessment of memory and quality of life.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These findings corroborate a systematic review 2 on computerized cognitive training, which found a significant improvement in the cognitive and psychological characteristics of healthy older adults. Likewise, the study by Ordonez et al, 6 involving cognitive training with computer games in the elderly, also observed positive effects in the assessment of memory and quality of life.…”
Section: Discussionsupporting
confidence: 89%
“…In this scenario, in a systematic review 2 on the use of tablets by the elderly, cognitive benefits were reported in most of the reviewed articles. In one of the studies, 3 which involved 16 elderly people, the authors concluded that electronic devices provided results similar to those of standard cognitive training.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…O design e a interface dos aparelhos também foram apontados como entraves para a infoinclusão como observado em estudos que mencionam que o tamanho reduzido da tela e dos ícones ou botões, assim como o touchscreen podem comprometer o bom desempenho no uso por parte de alguns idosos, em decorrência de deficiências sensoriais ou alterações psicomotoras (Sales et al, 2014). Desta forma, a baixa usabilidade, agregada a questões de acessibilidade, inteligibilidade e estrangeirismos podem se apresentar como obstáculos (Alvarenga et al, 2018) para a equidade digital, especialmente para usuários com baixa escolaridade.…”
Section: Discussionunclassified